2014
DOI: 10.1074/jbc.m114.592097
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Biochemical Insights into the Activation Mechanisms of Germinal Center Kinase OSR1

Abstract: Background: OSR1 modulates ion homeostasis and cell volume in mammal. Results: The CCT domain and ␣AL helix of OSR1 act together to suppress its basal activity, while WNKs and MO25 unlock such autoinhibition for full activation. Conclusion: OSR1 activity is regulated by autoinhibition, WNKs, and MO25. Significance: This work provides insights into the regulatory mechanisms of OSR1 activation to facilitate functional study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…αAL helices occur in diverse classes of kinases, e.g., EGF receptor (51), and are known to be inhibitory by sterically blocking the inward movement of αC to form the K-E ion pair. Recent work has shown that deletion of the αAL helix in OSR1 leads to enhanced kinase activity (52). Interestingly, the positions of SPAK WT and OSR1 WT αAL helices are incompatible with the position of the SPAK T243D activation loop (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…αAL helices occur in diverse classes of kinases, e.g., EGF receptor (51), and are known to be inhibitory by sterically blocking the inward movement of αC to form the K-E ion pair. Recent work has shown that deletion of the αAL helix in OSR1 leads to enhanced kinase activity (52). Interestingly, the positions of SPAK WT and OSR1 WT αAL helices are incompatible with the position of the SPAK T243D activation loop (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The scaffold protein Mo25/calcium binding protein 39 stimulates SPAK/OSR1 activity in vitro and seems to work synergistically with WNKs. 9 Amino acids important for SPAK/ OSR1 interactions with Mo25, including sites A-D Glu, Val, Tyr, and Trp/Glu/Trp in SPAK/OSR1 and Met260 in Mo25, are conserved in Fray and DmMo25, 9,36 and Fray and DmMo25 interact in Drosophila developmental processes. 37 We examined whether DmMo25 stimulates Fray activity by performing in vitro kinase assays using purified Drosophila proteins, DmMo25, Fray, and the N terminus of NKCC (encoded by Ncc69).…”
Section: Mo25 Is Required For Maximal Transepithelial Ion Transportmentioning
confidence: 99%
“…In this study, we were the rst to demonstrate that the common allele homozygotes of rs1384006 C > T of the OXSR1 gene were signi cantly associated with a higher exacerbation rate and the risk of FE in the nonsmoking asthmatics. OXSR1 has rarely been studied with regard to respiratory diseases, although it plays a role as a salt transportation, and cell volume control through ionic mechanisms [33,34] and ion transport by bronchial epithelial cells is essential for healthy airways. Imbalance of the transport system is closely related to the pathophysiology of asthma such as dysfunction of epithelial cells and smooth muscles.…”
Section: Discussionmentioning
confidence: 99%
“…OXSR1 is also involved in the regulation of immune responses by interacting with TNF receptor protein kinase C-θ (PKCθ), which is expressed by lymphoid tissues. [25,34] OXSR1 and WNK1 kinase, an upstream activator of OXSR1, are hardly detectable at basal activity, which may mean that WNK-OXSR1 signaling is regulated tightly in normal physiological conditions. [34] Interestingly, this genetic effect of rs1384006 C > T was not found in the smoker asthmatics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation